Anatomical Location of the Mesencephalic Locomotor Region and Its Possible Role in Locomotion, Posture, Cataplexy, and Parkinsonism - Sherman, David; Fuller, Patrick M.; Marcus, Jacob; Yu, Jun; Zhang, Ping; Chamberlin, Nancy L.; Saper, Clifford B.; Lu, Jun (Frontiers in Neurology, 2015)
The mesencephalic (or midbrain) locomotor region (MLR) was first described in 1966 by Shik and colleagues who demonstrated that electrical stimulation of this region induced locomotion in decerebrate (intercollicular transection) cats. The pedunculopontine tegmental nucleus (PPT) cholinergic neurons and midbrain extrapyramidal area (MEA) have been suggested to form the neuroanatomical basis for the MLR, but direct evidence for the role of these structures in locomotor behavior has been lacking. Here we tested the hypothesis that the MLR is composed of non-cholinergic spinally-projecting cells in the lateral pontine tegmentum (LPT). Our results showed that putative MLR neurons medial to the PPT and MEA in rats were non-cholinergic, glutamatergic and express the orexin (hypocretin) type 2 receptors. Fos mapping correlated with motor behaviors revealed that the dorsal and ventral MLR are activated, respectively, in association with locomotion and an erect posture. Consistent with these findings, chemical stimulation of the dorsal MLR produced locomotion whereas stimulation of the ventral MLR caused standing. Lesions of the MLR (dorsal and ventral regions together) resulted in cataplexy and episodic immobility of gait. Finally, trans-neuronal tracing with pseudorabies virus (PRV) demonstrated disynaptic input to the MLR from the substantia nigra via the MEA. These findings offer a new perspective on the neuroanatomic basis of the MLR, and suggest that MLR dysfunction may contribute to the postural and gait abnormalities in Parkinsonism.